1999
DOI: 10.1207/s15327914nc352_3
|View full text |Cite
|
Sign up to set email alerts
|

Vegetables, Fruits, and Related Nutrients and Risk of Breast Cancer: A Case-Control Study in Uruguay

Abstract: To evaluate whether the protective effect associated with vegetables and fruits in breast cancer could be explained by nutrients and bioactive substances present in these plant foods, we carried out a case-control study in Uruguay including 400 cases and 405 controls. The intake of vegetables, fruits, and related nutrients was estimated with a food frequency questionnaire on 64 food items. This questionnaire allowed the calculation of total energy intake, and nutrients were calorie adjusted by the residuals me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(91 citation statements)
references
References 24 publications
5
82
0
4
Order By: Relevance
“…At pH [ 5, the completely dissociated microspecies is prevalent. Other microspecies (2,5,6,8) in which the cyclic nitrogen is protonated are in negligible percentage with respect to others. The pK a prediction of Betalamic Acid obtained by empirical methods Marvin and Epik is really consistent with results of Gandía-Herrero et al [16].…”
Section: Prediction Results Bias Factor and Accuracy Factormentioning
confidence: 88%
See 1 more Smart Citation
“…At pH [ 5, the completely dissociated microspecies is prevalent. Other microspecies (2,5,6,8) in which the cyclic nitrogen is protonated are in negligible percentage with respect to others. The pK a prediction of Betalamic Acid obtained by empirical methods Marvin and Epik is really consistent with results of Gandía-Herrero et al [16].…”
Section: Prediction Results Bias Factor and Accuracy Factormentioning
confidence: 88%
“…The contents of these substances in plants can be affected by many factors, such as season, regional differences and methods of cultivation and conservation (light, humidity, temperature, time). Epidemiological studies have shown that diets rich in plant-based foods help to prevent many diseases such as cardiovascular, metabolic, neurodegenerative and inflammatory [2][3][4]. Among the 1000s of different phenolic compounds, terpenoids, and sulfur-containing compounds, capable of reducing power and interfering in the redox processes modulated by cells [5][6][7], the Betalains, present in the plant kingdom, especially in Chenopodiaceae plants belonging to the Caryophyllales order, such as the prickly pear (Opuntia genus) and red beet (Beta vulgaris) as the main dietary sources, are compounds with high antioxidant (radical scavengers) capability of preventing the oxidation of biological molecules mediated by oxygen and free radicals and therefore can protect against diseases related to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies confirmed that phytosterols have hypocholesterolemy, anti-inflammatory and anti-carcinogenic effects (Awad et al, 2007;Ronco et al, 1999;Berges et al, 1995). Therefore, phytosterols have been added to several functional food products such as yoghurt, milk (Lagarda et al, 2006), and some vegetable oils (Ntanios, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies of folate and vitamin B 12 status and breast cancer have indicated a negative association between folate intake and risk of breast cancer (Graham et al, 1991;Freudenheim et al, 1996;Ronco et al, 1999;Zhang et al, 1999;Rohan et al, 2000), as well as a negative association between vitamin B 12 status and risk of breast cancer (Wu et al, 1999) and DNA damage (Fenech et al, 1998). The inverse association between folate status and breast cancer risk has been particularly strong among women who consumed alcohol (Sellers et al, 2001;Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%